WOMEN AS HIDDEN FIGURES IN MALE HEGEMONY: GENDER AND RACIAL IDEOLOGIES IN HIDDEN FIGURES - HUNG-CHANG LIAO; YA-HUEI WANG (LINGUISTICA, 2022)
This study intended to use the film Hidden Figures as a case study to examine how Black women were discriminated against in multiple ways: in terms of racism and sexism, and even classism. To further analyze how Black women, here Mary Jackson, Dorothy Vaughan, and Katherine Johnson, had limited access to employment and received lower wages as well, the study used the film Hidden Figures as a case study to consider how Black women allowed themselves to be treated subordinately and tolerated unequal treatment in the workplace in order maintain their job for the sake of their family. To complete this goal, after conducting a thorough literature review on racial discrimination, gender discrimination, Black feminism, and intersectional hierarchy, the study used a descriptive qualitative analysis and a latent-content analysis of Hidden Figures to examine how, in the 1960s and 1970s, Black women were disciplined and deprived of the opportunity to seek higher education or demonstrate their leadership skills. Moreover, this study demonstrated that, although they had been the object of personal or institutional discrimination, these Black women managed to survive in a multifaceted discriminatory hierarchal society. Finally, by resisting, they found success in their workplace.